A Coupling Coordination Analysis of Population Characteristics and Carbon Emissions in Sichuan Province, China - Zhang, Yu (INTI International University, 2025)
In the context of global climate change, carbon emissions have become one of the most pressing challenges to sustainable development in human society. This study examines population characteristics and carbon emission trends in Sichuan Province under China's "dual carbon" goals (carbon peaking and carbon neutrality). By establishing an indicator system linking demographic factors—including total population, age structure, urbanization level, income levels, consumption patterns, and population density—to carbon emissions, we applied a coupling coordination model to analyze Sichuan's demographic changes from 2004 to 2021. The results show that while the comprehensive coupling coordination index fluctuated annually, its overall upward trajectory from 0.09 in 2004 to 0.61 in 2021 aligns with the general trend of improved coordination. This indicates significant progress from extreme imbalance to basic coordination. To accelerate achieving the dual carbon targets, it is crucial to strengthen population management policies, develop measures addressing demographic structures, enhance population quality, and implement targeted strategies for sustainable development.